PENGARUH KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Tutik Lestari, Edi Wibowo & Sunarso (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the significance of the effect of theleadership, work culture and motivation on employees performance and to analyze thesignificance of the effect of leadership and work culture on employees performancemoderated by motivation. This research is a survey of employees of PT Sakura Garmentin Surakarta. The study population of employees of PT Sakura Garment Surakartatotaling 228 people. Sample study 68 people with technique of proportional clusterrandom sampling. Data collection technique used questionnaire and literature. Datawere analyzed used multiple linear regression and test of absolute difference. The resultsshowed that the leadership has a significant effect on employees performance. Workculture has significant effect on employees performance. Motivation has a significanteffect on employees performance. Motivation does not moderate the effect of leadershipon employees performance. Motivation does not moderate the effect of corporate cultureon employees performance.Keywords: leadership, work culture, motivation, performance